2021
DOI: 10.1007/s40615-021-00975-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Casual Sex Amidst Vulnerability to HIV Among ACB Heterosexual Men in Ottawa and Windsor, Ontario Canada

Abstract: Heterosexual exposure is the second highest means of HIV transmission; and African, Caribbean, and Black (ACB) men face greater risks. Black men can reduce the disproportionately high HIV prevalence in their communities by changing their socially misconstrued masculine role. We analysed factors predisposing heterosexual ACB men to risky sexual behaviour, particularly multiple casual sex partnerships in Ottawa and Windsor, Ontario, Canada. We employed quantitative datasets from a broader mixed methods study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A majority was within age range, 15-49 years. In Windsor, 43.59% (n=68) were in the age range of: 15-29 years, and 20.51% (n=32) were in 30 -39 years of age, and those in category of 40-49 years were 9.6% (n=15). In Ottawa, 51.42% (n=108) were 15 -29 years old and 23.81% (n=50) were 30-39 years of age, and 18.10% (n = 38) were in the 40-49 years age category.…”
Section: A Descriptive Statistics Of Demographic Characteristicsmentioning
confidence: 94%
See 2 more Smart Citations
“…A majority was within age range, 15-49 years. In Windsor, 43.59% (n=68) were in the age range of: 15-29 years, and 20.51% (n=32) were in 30 -39 years of age, and those in category of 40-49 years were 9.6% (n=15). In Ottawa, 51.42% (n=108) were 15 -29 years old and 23.81% (n=50) were 30-39 years of age, and 18.10% (n = 38) were in the 40-49 years age category.…”
Section: A Descriptive Statistics Of Demographic Characteristicsmentioning
confidence: 94%
“…A comparable survey in the US showed that youth aged 13 -24 years made up 21% of new cases of HIV in 2018 (CDC, 2018). This is perhaps the case for young men in this age category in because sexual experimentation common among in this age class [42], [43], alongside drug abuse motivated by peer pressure and complacent attitudes towards HIV risks accentuated by generational changes in HIV epidemic [44]. While these statistics is troubling, the situation is worse for ACB heterosexual men in this age category because the ACB community is already disproportionately affected by HIV due to factors highlighted earlier on.…”
Section: A Age Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, misconceived ideas about HIV can reinforce social stigma against people living with HIV and deter health-seeking behaviours related to HIV [ 10 , 17 , 18 ] Stigma creates barriers for people to get tested, which is a significant challenge for the prevention of HIV among HBM in Ontario [ 10 ]. Furthermore, these misconceptions may reinforce the belief that condom use is not necessary, resulting in unprotected sex and a higher risk of HIV [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the existing research on Afro-Canadian leaders is concentrated in Toronto, Montreal, and Halifax (Arthur et al 2012, Austin 2007, Johnson 2016, Kitossa 2019, McDuffie 2016. Of the research on African Canadian populations in Ottawa, a majority are related to health issues such as HIV (e.g., Omorodion et al 2021, Mbuagbaw et al 2020 or specific ethnic groups such as Somali (e.g., Lagace et al 2012) including work by graduate students (Abdulle 2000, Farah 2011, Mohamed 2007, Kenny 2008.…”
Section: Significance Of Researchmentioning
confidence: 99%